Gender Equality and Gender Mainstreaming – Achievements and Issues - Novikova, Irina (Sociologija. Mintis ir veiksmas, 2004)
The Baltic States have made a considerable progress in meeting gender equality directives of European Union (EU) in line with the proclaimed fundamental democratic values of Member States and of Union enlargement policy. Despite progress, equality in day-to-day life is still undermined by structural gender in equalities and unequal access to rights enjoyed by women and men in practice. The issues of women’s unemployment, poverty, age, and ethnic background clearly manifest the political preferences by national governances of the Baltic States for the expert-bureaucratic model, based on ‘integrationist’ approach to gender equality policies and gender mainstreaming, adapted to the national neo-liberal modifications of the former Soviet gender contract.
Keywords: gender equality; rights; gender mainstreaming; Baltic states